Comparison of leisure satisfaction with pickleball for adult players - Recky Ahmad Haffyandi; Akhmad Amirudin; Ma'ruful Kahri (Lambung Mangkurat University, 2024)
Pickleball are interesting sport because there is no age limit to play this sport. However, it is necessary to further explore whether players, especially seniors, get satisfaction from the physical, psychological, and social benefits of the sport. The purpose of this study is to analyze the leisure satisfaction arising from pickleball for the elderly. And analyzing differences in leisure satisfaction based on gender of the elderly. The research method is survey research, descriptive research type with a quantitative approach using purposive sampling the sample used was 30 active players in South Kalimantan with ages over 50 years. The research instrument is Leisure Satisfaction Scale (LSS) with psychological, educational, social, relaxation, physiological, and aesthetic indicators. Data collection by distributing questionnaires online then data analysis techniques using average testing each component and using independent sample Ttest. The results showed that the social and relaxation aspects had the highest value followed by other aspects. And there are significant differences in leisure satisfaction based on gender with a P-value of psychological indicators (0.001), education (0.000), social (0.009), relaxation (0.003), physiological (0.015) and aesthetics (0.025). This study concludes that playing pickleball provides leisure satisfaction for elderly individuals, with differences in satisfaction levels based on gender.